2021
DOI: 10.3390/app11083387
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Calcium Phosphate from Fish Discards and By-Products

Abstract: Every year, millions of tons of fish waste are generated from fishing activities, and a similar amount is discarded and returned to the sea as unwanted catches. This material can be used as a biological source for many potential new added-value products, such asobtaining hyaluronic acid from fish eyeballs or extracting collagen from fish skin, but there are not many utilities for fish bones yet. This work tackles the transformation of fish discards into calcium phosphates. Discards from scorpionfish (Scorpaena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…2− [109]. The decreasing of the Ca/P ratio in all three cases with the increase of the calcination temperature could be attributed to a partial transformation of the HA phase in β-TCP and, consequently, to the formation of BCP compound.…”
Section: Elemental Compositionmentioning
confidence: 84%
See 4 more Smart Citations
“…2− [109]. The decreasing of the Ca/P ratio in all three cases with the increase of the calcination temperature could be attributed to a partial transformation of the HA phase in β-TCP and, consequently, to the formation of BCP compound.…”
Section: Elemental Compositionmentioning
confidence: 84%
“…Heavy metals (like Hg, Cd, and Pb), which are present in fishes, should be avoided in any products dedicated to humans because of their harmful effects, such as toxic or carcinogenic behavior. For the three fish species, the authors found out that the amount of these elements present in BCP powder was lower than the maximum permitted value for organic bone implant materials (Cd: 0.68 ppm, Pb: 1.6 ppm, Hg: 0.04 ppm) [109].…”
Section: Elemental Compositionmentioning
confidence: 88%
See 3 more Smart Citations